SISTEM PAKAR KALKULATOR GULA DARAH BERBASIS WEBSITE MENGGUNAKAN METODE FORWARD CHAINING - tampubolon, abdul chafid; Handoko, Koko (Computer Science and Industrial Engineering, 2020)
People with very severe disease or diabetes who need an increased increase, from close monitoring, received 2,866 who contracted blood sugar in 2007. One of the results of the study increased the resources used as an energy source controlled by insulin, according to the British diabetes agency, using A person's normal blood sugar level during fasting is 4.0 to 5.4 mmol / L (72 to 99 mg / DL), meanwhile. A person's normal blood sugar level two hours after eating is 7.8 mmol / L (140 mg / dL), but for people with hyperglycemia or high blood sugar levels. will have a sugar level of more than 180 mg / dL, while for sufferers of hypoglycemia or low blood sugar levels. will have blood sugar below 70 mg / dL. mmol / L is a unit of molecules to calculate the number of blood sugar molecules per liter, while mg / dL is a unit of measurement of milligram weight per deciliter for measurement of blood sugar levels. Blood sugar levels contain sugar or sugar in the blood. While constantly changing changes, sugar levels need to be maintained within normal limits so that disruption does not occur in the body. Blood sugar levels are needed by the intake of nutrients from food or drinks, especially carbohydrates, also the amount of insulin and the sensitivity of body cells to insulin. Blood sugar levels that are too high or too low will have a negative impact on health, both in the short and long term.